1986
DOI: 10.1111/j.1432-1033.1986.tb09607.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical quantification of sarcoplasmic reticulum Ca-ATPase, of calsequestrin and of parvalbumin in rabbit skeletal muscles of defined fiber composition

Abstract: Antibodies directed against purified Ca-ATPase from sarcoplasmic reticulum, calsequestrin and parvalbumin from rabbit fast-twitch muscle were raised in sheep. The specificity of the antibodies was shown by immunoblot analysis and by enzyme-linked immunoadsorbent assays (ELISAs). IgG against the sarcoplasmic reticulum CaATPase inhibited the catalytic activities of Ca-ATPase from fast-twitch (psoas, tibialis anterior) and slow-twitch (soleus) muscles to the same degree. In non-equilibrium competitive ELISAs the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 50 publications
6
72
0
Order By: Relevance
“…In agreement with the published difference in Ca-ATPase content between EDL and SOL [5,14,28], we found for the euthyroid condition a 7-fold higher Ca-ATPase activity in EDL as compared to SOL, and the maximal T3-dependent stimulation of this activity (hyper-versus hypothyroid) was 6-fold for SOL and 1.5-fold for EDL (see legend to Fig. 3 for data).…”
Section: Mrna Levels Versus Ca-a Tpase Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the published difference in Ca-ATPase content between EDL and SOL [5,14,28], we found for the euthyroid condition a 7-fold higher Ca-ATPase activity in EDL as compared to SOL, and the maximal T3-dependent stimulation of this activity (hyper-versus hypothyroid) was 6-fold for SOL and 1.5-fold for EDL (see legend to Fig. 3 for data).…”
Section: Mrna Levels Versus Ca-a Tpase Activitysupporting
confidence: 91%
“…Measurement of SR Ca-ATPase activity, or coupled Ca 2 + -transport, in muscle homogenates or isolated SR [1][2][3][4]17], as well direct determination of enzyme levels [5] and electron microscopy [6] has shown that Ca-ATPase levels are increased by T3 up to 6-fold in slow muscle and 1.5-fold in fast muscle. Slow muscle fibers (type I) express the cardiac isoform of the CaATPase (designated type I in this paper), and fast muscle fibers (type II) express 5 to 7 times higher levels of the somewhat more active isoform of the Ca 2 + pump (designated type II) [5,14,28]. Both isoforms are encoded by separate genes [7,8], and it is not known whether T3 merely stimulates the expression of the isoform already present in a muscle fiber, or that the two isoforms are differently affected.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue contents of CaZ+-ATPase and calsequestrin were immunochemically determined by the use of a sandwich enzyme-linked immunoadsorbent assay (ELISA) [20]. The competitive ELISA used for distinguishing isoforms of Ca2…”
Section: Methodsmentioning
confidence: 99%
“…ATPase was the same as in [20]. The conditions for measurement of phosphoprotein formation and for the spectrophotometric assay of Ca2+,Mg2+-ATPase activity in total SR 7-8 (S), 12-16 (14), 16-20 (lS), 20-24 (22), 24-28 (26 …”
Section: + -mentioning
confidence: 99%
See 1 more Smart Citation